18th International Parallel and Distributed Processing Symposium, 2004. Proceedings.
DOI: 10.1109/ipdps.2004.1303248
|View full text |Cite
|
Sign up to set email alerts
|

XTC: a practical topology control algorithm for ad-hoc networks

Abstract: The XTC ad-hoc network topology control algorithm introduced in this paper shows three main advantages over previously proposed algorithms. First, it is extremely simple and strictly local. Second, it does not assume the network graph to be a Unit Disk Graph; XTC proves correct also on general weighted network graphs. Third, the algorithm does not require availability of node position information. Instead, XTC operates with a general notion of order over the neighbors' link qualities. In the special case of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
170
0
2

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 28 publications
0
170
0
2
Order By: Relevance
“…As shown in [11], if neighborhood orderings are distance-based (as in (1)), then G XT C is connected. Note that according to this definition, each node u orders its neighbors in increasing order of distance, breaking ties using ids.…”
Section: G Xt C May Be Disconnectedmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in [11], if neighborhood orderings are distance-based (as in (1)), then G XT C is connected. Note that according to this definition, each node u orders its neighbors in increasing order of distance, breaking ties using ids.…”
Section: G Xt C May Be Disconnectedmentioning
confidence: 99%
“…It is shown in [11] that G XT C is symmetric provided G is and this is independent of ≺. It is also shown that if G is a Euclidean graph and ≺ u is defined as…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations